APAKAH INVESTOR MEMBERIKAN PENGHARGAAN ATAU SANKSI TERHADAP PRAKTIK PENGHINDARAN PAJAK? TINJAUAN LITERATUR REVIEW - Muarif Leo; Abdul Gafur; Risna Risna; Misran Misran; Andriani Saputri (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to analyze how investors respond to corporate tax avoidance practices and to identify whether the capital market tends to reward or penalize such practices. The study employs a Systematic Literature Review (SLR) method in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The literature was selected based on the following criteria: a population of publicly traded companies; the phenomena of tax avoidance and tax aggressiveness; the context of capital market consequences; and relevance to the research questions. The analysis was conducted by synthesizing findings from previous studies that link tax avoidance practices to investor responses and corporate market value. The results indicate that investor responses to tax avoidance are not uniform. Investors may reward companies when tax avoidance is perceived as an efficiency strategy that increases after-tax cash flow and corporate value. Conversely, investors may penalize companies when such practices are viewed as increasing risk, reducing transparency, and reflecting opportunistic management behavior. The findings indicate that corporate governance, audit quality, institutional ownership, political connections, social responsibility, and investor protection play a role in shaping market responses. This study confirms that the impact of tax avoidance on capital markets is contextual.